Homozygosity Mapping and Whole Exome Sequencing Reveal a Novel Homozygous COL18A1 Mutation Causing Knobloch Syndrome - Haghighi, Alireza (PLoS One, 2014)
The aim of this study was to identify the genetic basis of a chorioretinal dystrophy with high myopia of unknown origin in a child of a consanguineous marriage. The proband and ten family members of Iranian ancestry participated in this study. Linkage analysis was carried out with DNA samples of the proband and her parents by using the Human SNP Array 6.0. Whole exome sequencing (WES) was performed with the patients’ DNA. Specific sequence alterations within the homozygous regions identified by whole exome sequencing were verified by Sanger sequencing. Upon genetic analysis, a novel homozygous frameshift mutation was found in exon 42 of the COL18A1 gene in the patient. Both parents were heterozygous for this sequence variation. Mutations in COL18A1 are known to cause Knobloch syndrome (KS). Retrospective analysis of clinical records of the patient revealed surgical removal of a meningocele present at birth. The clinical features shown by our patient were typical of KS with the exception of chorioretinal degeneration which is a rare manifestation. This is the first case of KS reported in a family of Iranian ancestry. We identified a novel disease-causing (deletion) mutation in the COL18A1 gene leading to a frameshift and premature stop codon in the last exon. The mutation was not present in SNP databases and was also not found in 192 control individuals. Its localization within the endostatin domain implicates a functional relevance of endostatin in KS. A combined approach of linkage analysis and WES led to a rapid identification of the disease-causing mutation even though the clinical description was not completely clear at the beginning.